Novel insights into RabA2b intracellular localization suggest a role in plasmodesmatal function - Ambastha, Vivek; Tidhar, Dafna; Matityahu, Ifat; Leshem, Yehoram (Frontiers in Plant Science, 2025)
Plasmodesmata (PD) are microchannels that bridge together neighboring plant cells by connecting their plasma membranes to each other. Thus, the PD establish the symplast, a cytoplasmic continuum that allows free transport of water and other small molecules between cells. Also, PD communicate with the cytoplasm via intercellular trafficking. Rab small GTPases are key regulators of vesicle trafficking, though surprisingly, their role in PD targeting and trafficking is still obscure. Here we show, for the first time, that the RabA member, RabA2b, associates with the PD. Furthermore, its overexpression in Arabidopsis facilitates symplastic mediated transport. Additionally, during osmotic stress, the presence of RabA2b was observed along the Hechtian Strands (HS) as well as at HS-cell wall docking sites. Our findings provide new insights into the potential involvement of RabA2b in PD permeability regulation and mediation of the symplast integrity, necessary for water maintenance during water stresses.